Enhancing the Electronic Consumer’s Right to Information - Azzeddine, Chouar; Younes, Bensalem (Journal of Ecohumanism, 2025)
This paper emphasizes the importance of enhancing consumer awareness of digital media rights in light of the rapid expansion of e-commerce and the growing dependence on online purchasing. It examines the pivotal role of media in informing consumers about their digital rights, including access to accurate and transparent information on goods and services, protection from misleading advertising, and the right to remedies such as refunds and replacements. By reinforcing the media’s educational function, the study highlights its contribution to fostering an informed consumer culture that supports rational purchasing behavior and promotes ethical standards among businesses. Ultimately, access to reliable information is presented as a key mechanism for protecting consumer rights in digital environments and as a fundamental element in strengthening trust between consumers and online markets.